Modelling of an Actuator in the Vacuum Control System of an Autonomous Milking Machine (Agricultural Engineering, 2016)
Design intents for an actuator of the suction pressure control system in an autonomous milking machine were presented. For determination of its dynamic properties step characteristic was taken. The considered object was described with transmittance and thermodynamic models. Models were identified and their parameters were adjusted. Computer simulation was carried out in MATLAB®-Simulink. Analysis of research results proved that the thermodynamic model allows more detailed reflection of dynamic characteristic of the real object. Its degree of imperfections is 0.99%. For the transmittance model a degree of imperfection with the value of 2.02% was obtained.